Pengaruh Gaya dan Kebiasaan Belajar terhadap Kemampuan Berfikir Kritis Matematika - Erlando Doni Sirait (SAP (Susunan Artikel Pendidikan), 2019)
This study aims to determine the influence of learning styles on the ability to think critically mathematics, the influence of learning habits of critical thinking skills of mathematics, and the influence of interaction of learning styles and habits of critical thinking skills of mathematics. The research method used is expose facto method with two way ANOVA, with the number of samples as many as 90 people. The instrument used is the instrument of learning style questionnaire and learning readiness and essay in understanding the concept of mathematics. From this research, it can be concluded that: (1) There is significant influence of Learning Style to Student's Creative Thinking Ability, (2) There is a significant influence of Learning Habit to Student's Creative Thinking Ability, (3) There is no significant effect of Style Interaction and Learning Habits of Student Maths Creative Thinking Ability. The implication of this research is that there is no influence of students 'learning styles and students' learning habits on the ability to think creatively math significantly. Thoroughly creative thinking ability of math students who learn with visual learning styles, audio and kinesthetic learning styles do not differ much, it's just kinesthetic learning style more dominate well. So to strengthen kinestetik learning style with high learning habits in teaching and learning activities, so that students can be more leverage in understanding the concept of mathematics.